Personality and Psychological Factors of Problematic Internet Gamers Seeking Hospital Treatment - Seong, Wonshik; Hong, Ji Sun; Kim, Soyoung; Kim, Sun Mi; Han, Doug Hyun (Frontiers in Psychiatry, 2019)
Introduction Previous studies on internet gaming disorder (IGD) have reported an association between personality traits and impulsive or problematic use of the internet or internet games, although the results obtained have been inconsistent. We hypothesized that personality traits would be associated with the choice to play internet games. In addition, psychological status would be associated with seeking treatment in the hospital for individuals with problematic internet game play. Methods Of the 429 participants recruited in the current study, 139 were infrequent-gamers, 138 were frequent gamers, and 152 were problematic gamers. Individuals who reported excessive internet game playing and visited the hospital for treatment in the current study were defined as the problematic internet gaming group. Hierarchical logistic regression analyses were conducted among each set of variables. Furthermore, participants’ demographic factors (i.e., sex, age, and years of education), personality traits (i.e., temperament and character), and psychopathological status (i.e., depression, anxiety, and attention deficit) were evaluated in a stepwise fashion. Results Temperament may be associated with internet game playing. Additionally, model 2, which comprised both demographic factors and personality traits, significantly enhanced the predictability of internet gaming, reaching an accuracy of 96.7%. Of the three models employed in the current study, model 2 and model 3, which was comprised of model 2 and the patient’s psychological status were associated with problematic internet gaming. Discussion The current study found that personality traits might be associated with online gaming. In addition, abnormal psychological status (especially, depressive mood and attention deficit) might lead individuals with problematic internet gaming to the hospital for treatment.